Readiness to Professional Self-Determination of Orphaned Adolescents in the Context of their Social Situation of Development - Aron, I.S. (Psihologo-pedagogičeskie issledovaniâ, 2018)
Discusses personal and socially significant problem of professional self-determination in the context of the social situation of development self-defining personality. Structural components of the social situation of development of professional self-defining of personality: objective (social context) and subjective (psychological readiness to professional self-determination). Emphasized the importance of psychological readiness (cognitive, activity, motivational and personal) for successful professional self-determination and its particular relevance for adolescents with sharpened social situations of development. The results of empirical research of psychological readiness to professional self-determination 43 adolescents-orphans, living in the Volga secondary boarding school for children-orphans and children left without parental care in the Republic of Mari El. With the help of specially selected complex of diagnostic methodologies for various components of psychological readiness to professional self-determination, it was found that for adolescent orphans may lack cognitive, activity, motivational and personal readiness. Differences with the comparison group (73 teenager placed with families) are statistically significant. The obtained data can serve as a basis for concept development and special technologies of psychological and pedagogical support of professional self-determination of adolescents-orphans. Обсуждены личностно и социально значимая проблема профессионального самоопределения в контексте социальной ситуации развития самоопределяющейся личности. Выделены структурные компоненты социальной ситуации развития профессионально самоопределяющейся личности: объективные (социальный контекст) и субъективные (психологическая готовность к профессиональному самоопределению). Акцентированы важность психологической готовности (когнитивной, деятельностной, мотивационной и личностной) для успешного профессионального самоопределения и ее особая значимость для подростков с обостренными социальными ситуациями развития. Представлены результаты эмпирического исследования психологической готовности к профессиональному самоопределению 43 подростков-сирот, воспитывающихся в Волжской средней общеобразовательной школе-интернате для детей-сирот и детей, оставшихся без попечения родителей, Республики Марий Эл. Было выявлено, что для подростков-сирот характерна недостаточная когнитивная, деятельностная, мотивационная и личностная готовность. Различия с группой сравнения (73 подростка, воспитывающиеся в семьях) по большинству показателей статистически значимы. Полученные данные могут служить основой для разработки концепции и специальных технологий психолого-педагогического сопровождения профессионального самоопределения подростков-сирот.